Design and Manufacturing of Wind Tunnel for Turbine Impeller Airfoil Testing - Karnova Yanel; Asmara Yanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
In this study, the design of a wind tunnel was carried out to observe airflow through an airfoil, streamlines and turbine blades. To accommodate this, in this study a design was made of an open return wind tunnel. In this case, an open circuit wind tunnel type will be made because the construction is simpler and the manufacturing costs are relatively cheaper compared to the closed circuit wind tunnel type. The Wind Tunnel is designed with Open CLosed Wind Tunnel (OCWT) type. The OCWT is designed to consist of fan and housing, diffuser, test section, contraction, honeycomb. The OCWT design uses an operating fan to circulate air into the test section. The maximum air speed in the Test Section is 5 m/s with a flow that is closed to laminar. The recommended diffuser has a dimension of 50 cm on the side that is attached to the test section and 52 cm on the side facing the fan with an inclination angle of 1.79o. The driver uses a 16 inch exhaust fan with a power of 74 W to make the flow in the Test Section stable at a speed of 2 m/s.